(3ebGdI aj EHWGd Cf GdYOO ZjQ eJfGg Ch ebGdI aj ZjQ GdeJfGgis - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3bGd jMji Hf YOi Hf RcQjG Efi deG hLOJ GcKQ GNhGffG ef eJadSai YUQfG eUQjf Ydi Cf GdXf HGdYOO Gfg Ph fgGjI s
(3BNQgG (B:s
(3adJYde Cf gPG GdPi GJi Hg djS efGbVkG deG bdfGg dGfG de fbd Gfg GPG de jhLO TF ef GLQ Gcd ahGLH Gf dG jhLO hdG ai Pdc Gdcd GjVkG JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1/4901) s
Keywords: (3GdadSaI hGdefWbs